2019
DOI: 10.1108/ejmbe-11-2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

Employee deviant behavior: role of culture and organizational relevant support

Abstract: Purpose The purpose of this paper is to increase the knowledge and understanding of organizational and supervisory support in the context of employee deviant workplace behavior (DWB) by examining the potential associations of employees’ cultural value orientations. This paper aims to: clarify DWB; review perceived organizational support (POS) and perceived supervisory support (PSS); discuss the meaning of employees’ cultural value orientations (individualism–collectivism, power distance and paternalism); use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 83 publications
(114 reference statements)
3
35
0
Order By: Relevance
“…In terms of identifying selected values that act as antecedents of deviant behavior and with regard to characteristics of culture that promote deviance, for instance, Zheng et al [18] found that in Machiavellian corporate culture that included dimension of low trust, control and status orientation employees exhibit counterproductive work behavior. Kalemci et al [19] found power distance and paternalistic cultural orientation interrelates with deviant behavior. Previous empirical research that orients on CVF cultural types, as Fulmore [20], finds hierarchy culture to encourage and clan culture to discourage ethical behavior, while results of Di Stefano et al [21] show lowest level of deviance to be in adhocracy and clan cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of identifying selected values that act as antecedents of deviant behavior and with regard to characteristics of culture that promote deviance, for instance, Zheng et al [18] found that in Machiavellian corporate culture that included dimension of low trust, control and status orientation employees exhibit counterproductive work behavior. Kalemci et al [19] found power distance and paternalistic cultural orientation interrelates with deviant behavior. Previous empirical research that orients on CVF cultural types, as Fulmore [20], finds hierarchy culture to encourage and clan culture to discourage ethical behavior, while results of Di Stefano et al [21] show lowest level of deviance to be in adhocracy and clan cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Collectivism is the extent to which individuals are integrated and cohesive with their groups and is a moral model in company and employee relations (Hofstede, 1998). Society in the collectivism culture tends to be more loyal and concerned with achieving group goals rather than their personal interests (Kalemci et al, 2019), helping each other (Pekerti and Sendjaya, 2010), Passive leadership and deviant behaviors resolving conflicts without destroying the group and conformity of behavior with group norms, such as regarding what behavior is acceptable in the group (Triandis, 2001). Moreover, if their behaviors deviate from group norms, they will lose their face (Triandis, 2001).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…However, there are still very few studies investigating the role of PD and collectivism in weakening/strengthening WDB (e.g. Kalemci et al, 2019). To the best of our knowledge, no studies have been done to investigate the moderating effect of cultural values on the relationship between passive leadership and deviant behaviors toward supervisors and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers (Kalemci, Kalemci-Tuzun, & Ozkan-Canbolat, 2019;Zakayo, 2018;Dessler, 1999;Fiorita, Bozeman, Young, & Meurs, 2007) have laid their focus on linking culture, employee satisfaction, commitment and performance. In the past decades, organizational culture was at the centre of research interest because of its influence on organizational processes (Rashid, Sambasivan, & Johari, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%